Accelerated Forced Degradation of Pharmaceuticals in Levitated Microdroplet Reactors. Issue 29 (30th April 2018) - Li, Yangjie; Liu, Yong; Gao, Hong; Helmy, Roy; Wuelfing, W. Peter; Welch, Christopher J.; Cooks, R. Graham
Abstract: Forced degradation is a method of studying the stability of pharmaceuticals in order to design stable formulations and predict drug product shelf life. Traditional methods of reaction and analysis usually take multiple days, and include LC‐UV and LC‐MS product analysis. In this study, the reaction/analysis sequence was accelerated to be completed within minutes using Leidenfrost droplets as reactors (acceleration factor: 23–188) and nanoelectrospray ionization MS analysis. The Leidenfrost droplets underwent the same reactions as seen in traditional bulk solution experiments for three chemical degradations studied. This combined method of accelerated reaction and analysis has the potential to be extended to forced degradation of other pharmaceuticals and to drug formulations. Control of reaction rate and yield is achieved by manipulating droplet size, levitation time and whether or not make‐up solvent is added. Evidence is provided that interfacial effects contribute to rate acceleration. Abstract : Traditional forced degradation of drug substances and drug products can take days to weeks but accelerated reaction/analysis of active pharmaceutical ingredients was achieved within minutes using Leidenfrost droplets and MS analysis. Lifetimes and sizes of the droplets and degree of solvent evaporation control reaction rate and product yield. Interfacial effects increase reaction rates in small droplets.